Ação rescisória no processo coletivo - Piaz, Livia Cipriano Dal (2008)
The subject Motion for annulment of judgment in class action has been chosen because, notwithstanding its importance, there is a lack of respective approach in specific monograph. The scope is to establish a parallel between the known discussions that surround the motion for annulment of judgment in the ordinary civil procedure and those that belongs exclusively to class action, aiming at better structuring the suitability of such lawsuit in claims related to the defense of transindividual rights. Accordingly, this study consists of three parts. Firstly, the study tries to put into context the origin of the need to protect mass conflicts, clarify the concept of collective rights, as well as its principles and applicable legal rulings. The second part is dedicated to court decision and res judicata, considering that we understand it to be the essential introduction to the study of motion for annulment of judgment. In this perspective, it is convenient to organize the chapter as of the general analysis of legal opinion, highlighting court decisions based on the traditional procedural doctrine, and pointing out the relevant circumstances found in class action disputes. In relation to res judicata, however, due to the richness of the work involving class action, we understand to be more adequate to bring only general considerations towards its formation in individual disputes, so we may cover in a more specific way the different aspects of res judicata of class action judgments. Finally, the last chapter attempts to point out the main issues related to the motion for annulment of judgment, analyzing in each aspect if the applicability of the traditional rules in class action should be taken into consideration to find out not only the similarities, but mainly, the aspects in which the motion for annulment of judgment filed collectively is and should be different